Church and Capitalism - Torre, Comte (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1949)
There have been many quotations made these days from an article of the Church and capitalism which appeared in the « Osservatore Romano » under the signature of its director, the Count della Torre. We are giving here some extracts.